Towards checking consistency and completeness of legal knowledge bases - Sinkevičiūtė, Sigita (Lietuvos matematikos rinkinys, 1998)
The paper considers consistency and completeness requirements for rule-based knowledge bases (KB) and their verification and validation (V&V) methods, discusses specific features of legal KB. The paper discusses possible modification of V&V methods with respect to these features, in order methods to be successfully used for legal KB.